The Effect of Multiple Choice Test And Scoring Technique on The Question Reliability of Biology Class at SMU - Zulmiati Zulmiati (Phinisi Integration Review, 2020)
This research was ex-post facto research with comparative, which aimed at examining the effect of multiple choice form and scoring technique on the question reliability of biology class at SMA Negeri 3 Bulukumba. The population of the research ware all of the students at SMAN in Bulukumba academic year 2016/ 2017. While the target population of the research ware all of the students at SMAN 3 Bulukumba, SMAN 4 Bulukumba, and SMAN 11 Bulukumba. The samples of the research were the students of class X at SMAN 3 Bulukumba, SMAN 4 Bulukumba, and SMAN 11 Bulukumba of the second  semester (semester 2) with the total sample of 475 students taken by using simple random sampling technique with reversion (sampling with replacemen). The instruments of the research were from of regular multiple choice and association multiple choice. The data were analyzed by using descriptive and inferential statistics analysis by using variant analysis (ANAVA) with the implementation of average cell model. The result of the research revealed that (1) there is a difference of reliability of biologi question of class X of multiple choice form between regular multiple choice and association multiple choice, (2) there was a difference of reliability of biology question of multiple choice form which employs scoring technique with correlation and multiple choice form which employs scoring technique with penalty, (3) there was no influence of interaction between of multiple choice form and scoring technique on biology question reliability of class X, (4) there was a difference of reliability of biologi question of class X of multiple choice form between regular multiple choice and association multiple choice by using scoring technique without correction, (5) there was a difference of reliability of biologi question of class X of multiple choice form between regular multiple choice and association multiple choice by using scoring technique with penalty, (6) there was a difference of reliability of biologi question of class X of multiple choice form between scoring technique with correction and scoring technique with penalty for regular multiple choice, and (7) there was a difference of reliability of biology question of class X of multiple choice form between scoring technique with correction and scoring technique with penalty for association multiple choice.